The Effect of Device Type on Buying Behavior in Ecommerce: An Exploratory Study - Fabian, Nicolai Etienne (Student Undergraduate Research E-journal!, 2017)
In this research, the effect different devices (smartphone, tablet, desktop) have on purchase behavior in ecommerce was explored. With an innovative combination of web analytics (Google Analytics/Hotjar) and a customer survey, a field experiment was conducted on the website of a Dutch retailer. It was found that smartphone devices limit the customer in ecommerce, while in the customer purchase journey several devices are used for different tasks at different times. The innovative approach used allows identification of different variables and their implications and effects on consumer behavior in web environments.